PENGARUH KOMPETENSI, KOMITMEN ORGANISASI DAN KOMUNIKASI KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Koperasi Artha Gemilang Kencana) - Ni Nyoman Suryani; Ni Wayan Eka Mitariani; Ni Kadek Kartika Wameda (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
The best performance requires directed management of human resources through various kind of policies that can adjust the common interests between the employees and company. This research aims to recognize the influence of competence, organizational commitment, and work communication on employee performance at the Koperasi Artha Gemilang Kencana. The population in this research were employees who worked at the Koperasi Artha Gemilang Kencana, totaling 35 people. The sampling of this research used is the technique of samping jenuh, so that the number of samples in this research were 35 employees. The data analysis technique used to answer the hypothesis is multiple linear regression analysis. The results of this research indicate that competence has a positive and significant influence on employee performance at the Koperasi Artha Gemilang Kencana. The organizational commitment has a positive and significant influence on employee performance in the Koperasi Artha Gemilang Kencana. The work communication has a positive and significant influence on employee performance at the Koperasi Artha Gemilang Kencana.